Penerapan Pendekatan Realistic Mathematics Education (RME) Berbantuan Media Powerpoint terhadap Hasil Belajar Matematika Ditinjau dari Gaya Belajar Siswa Kelas IVA SD Negeri 2 Wameo - L.M. Sahbudin Pratama (Journal on Education, 2024)
This research aims to increase the activities of teachers, students and learning outcomes in mathematics subjects through the application of the Realistic Mathematics Education (RME) approach assisted by PowerPoint media in terms of learning styles. This research is Classroom Action Research (PTK). The subjects of this research were teachers and students of class IVa SDN 2 Wameo, the number of students was 30 people. The types of data in this research are qualitative data and quantitative data. This research shows the following results: (1) the application of the Realistic Mathematics Education (RME) approach can increase teacher activity by 92.71% (good category), far above the predetermined success indicator, namely ≥75% (good category) . (2) The application of the Realistic Mathematics Education (RME) approach can increase student learning activities, namely 76.27% (good category), which is above the success indicator, namely ≥75% (good category). (3) Applying the Realistic Mathematics Education (RME) approach can improve mathematics learning outcomes, namely 96.67% (complete category), far above the success indicator, namely ≥85% (complete category).